Nitrogen recycling in mixed pastures of Calopogonium Mucunoides and Brachiaria Decumbens - Seiffert, Nelson Frederico; Zimmer, Ademir Hugo; Schunke, Rosa Maria; Behling-Miranda, Cezar Heraclides (Pesquisa Agropecuaria Brasileira, 2014)
The nitrogen (N2) recycling in single Brachiaria decumbens and mixed with Calopogonium mucunoides pastures, under continuous grazing was studied. The growth of grass and legume biomass, and the amount of N mobilized by the pasture plants to the biomass were recorded. Additionally, measurements of total nitrogen and ammonium + nitrate were obtained in the soil profile from layers of 0, 20, 50, 100, 160, 200 and 250cm of depth. The grass in the mixed pasture mobilized 105.57 kg/ha of N/year from the soil to the plant biomass, and the legume added more 81.37 kg/ha of N. The single pasture of Brachiaria decumbens recycled from soil to biomass by growth of 123.10 kg/ha of N/year under the same conditions, and a significant difference- (P < 0.05) of 63.84 kg/ha of N/year was added to the soil-pasture system by the legume. The recycled N resulted in significant increase (P < 0.05) in N and crude protein content in the forage. The legume was also responsible for a significant(P < 0.05) increase in the total N content of the soil surface layer, and of ammonium + nitrate content of the profile.